Biomimetic design of building facades: an evolutionary-based computational approach inspired by elephant skin for cooling in hot and humid climates - Hays, Nathan; Badarnah, Lidia; Jain, Anuj (Frontiers in Built Environment, 2024)
The built environment has been facing real challenges in managing energy demands with rising temperatures and other issues related to climate change. To meet carbon emissions target goals and to better manage resources, there is an urgent need to develop innovative and more energy-efficient cooling solutions. Nature provides a large database of adaptive and efficient thermal solutions that can be utilized in the design of buildings and their systems through biomimetic methods. Emerging biomimetic and computational approaches show promise in facilitating practical application efforts. The primary aim of this paper is to examine the translation of morphological features from elephant skin to building facades while optimizing their inherent cooling capabilities through computational design via evolutionary algorithms. This paper discusses some solutions from nature for cooling, provides a morphological basis for tackling environmental adaptation, and discusses potential applications to buildings in hot and humid climates. Understanding how morphological variations in this type of textured surface relate to environmental performance can help us design more effective and impactful passive cooling systems.